Calcium biofortified Schizophyllum commune and its relation to stunted growth among children / Razali, N. H., Roslan, N. H., and Nooh, H. M. - N. H, Razali; N. H, Roslan; H. M, Nooh (Faculty of Plantation and Agrotechnology, 2023)
The study investigated effect of concentration on biofortified Schizophyllum commune with Ca. The instrument of Atomic Absorption Spectroscopy (AAS) was used to determine the concentration. The concentration of elements generally increased over concentration gradients. As a side note, a series of calcium standard were made which is 1ppm, 2ppm, 3ppm, 4ppm, and 5ppm. The usage of AAS result a match concentration of prepared standard which are 1.098 mg/L, 2.054 mg/L, 3.01 mg/L, 4.003 mg/L, 4.947 mg/L respectively. The process of cultivating of S.commune was shorten by using a ready-made S.commune block. Two modes were done which are controlled and biofortified Ca. The three controlled S.commune were done in three replicate. The first, second, and third replicate result a Ca concentration of 0.328 mg/L, 0.224 mg/L, and 0.175 mg/L. For the Ca biofortified S.commune, the concentration obtained for S.commune that has sterile water:Ca (v/w) 1:3, 1:7, 1:11 is 0.329 mg/L, 0.276 mg/L, and 0.219 mg/L respectively. The difference between replicate 1 and ratio 1:3 is 0.001 mg/L, for replicate 2 and ratio 2 the difference is 0.052 mg/L, and for replicate 3 and ratio 3 are 0.044 mg/L. All difference shown an increasing Ca concentration. However, replicate 2 and ratio 2 are shown to have a big difference. This indicate that the by adding 7 grams of Ca nitrate, it could favourably increase the Ca concentration.